1997
DOI: 10.1002/(sici)1097-4679(199712)53:8<871::aid-jclp12>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between scores on anger measures and PTSD symptomatology, employment, and compensation-seeking status in combat veterans

Abstract: The interrelationship between the theoretically related constructs of anger and posttraumatic stress disorder (PTSD) symptoms was examined in a group of 42 combat veterans with PTSD using a multimeasure assessment strategy. Scores on several anger measures were found to be quite high in this sample and were significantly correlated with PTSD symptomatology. Furthermore, anger measures were found to be related to employment status independent of PTSD severity, but were not related to disability compensation-see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 16 publications
2
33
0
2
Order By: Relevance
“…Most people will experience at least one traumatic event during their lifetime (Kessler et al 1995), which can result in a myriad of negative consequences, including depression and anxiety disorders (Breslau et al 1991), low life satisfaction (Keim et al 2003), poor physical health (Buckley et al 2004), poor sleep quality (Krakow et al 2001), cognitive impairments (Koso and Hansen 2006), poor anger management (Frueh et al 1997), substance abuse (Kilpatrick et al 2003), and family and marital problems (Jordan et al 1992). Recent studies have revealed that stressful events that fall short of meeting the Diagnostic and Statistical Manual of Mental Disorders, fourth editiontext revision (DSM-IV-TR, American Psychiatric Association [APA] 2000) criteria for a traumatic event, such as relationship breakups, death of a loved one, and parents divorcing, can result in mental health symptoms comparable to those caused by traumatic events (Boals and Schuettler 2009;Gold et al 2005;Long et al 2008;Van Hooff et al 2009).…”
supporting
confidence: 80%
“…Most people will experience at least one traumatic event during their lifetime (Kessler et al 1995), which can result in a myriad of negative consequences, including depression and anxiety disorders (Breslau et al 1991), low life satisfaction (Keim et al 2003), poor physical health (Buckley et al 2004), poor sleep quality (Krakow et al 2001), cognitive impairments (Koso and Hansen 2006), poor anger management (Frueh et al 1997), substance abuse (Kilpatrick et al 2003), and family and marital problems (Jordan et al 1992). Recent studies have revealed that stressful events that fall short of meeting the Diagnostic and Statistical Manual of Mental Disorders, fourth editiontext revision (DSM-IV-TR, American Psychiatric Association [APA] 2000) criteria for a traumatic event, such as relationship breakups, death of a loved one, and parents divorcing, can result in mental health symptoms comparable to those caused by traumatic events (Boals and Schuettler 2009;Gold et al 2005;Long et al 2008;Van Hooff et al 2009).…”
supporting
confidence: 80%
“…Other factors that contribute to anger and aggression in PTSD are also discussed, including depression and alcohol use, as well as disruptions in core schemas related to trust, selfesteem, and power and control. The different assessments available for practitioners are then discussed, followed by As can be expected, a great deal of research has been conducted documenting the positive association between PTSD and anger [12][13][14][15]. Summarizing this literature empirically, Orth and Wieland conducted a meta-analysis and found that the mean effect size (r) between PTSD and anger was 0.48, indicating a large effect [16].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the physiological and psychological symptoms associated with PTSD have the potential to negatively affect both the physical and mental health of individuals (Friedman & Schnurr, ). Research indicates that PTSD is related to a number of mental health and behavioural disturbances such as depression (Lapierre, Schwegler, & LaBauve, ), increased alcohol use (Breslau, Davis, Peterson, & Schultz, ), anxiety disorders (Breslau et al , ), sleep quality (Krakow et al , ), anger management (Frueh, Henning, Pellegrin, & Chobot, ), quality of life (Zatzick et al , ) and cognitive impairments (Boals, ). Associations between PTSD symptoms and self‐reported physical health problems have also been found, such as associations with chronic pain (Beckham et al , ), health complaints (Zoellner, Goodwin, & Foa, ) and physical health symptoms (Norris, Slone, Baker, & Murphy, ).…”
Section: Outcomes Related To Traumatic Eventsmentioning
confidence: 99%